Pengaruh Model Pembelajaran Inkuiri pada Materi Larutan Penyangga Terhadap Hasil Belajar Siswa SMA - Rosida Rosida; Ratman Ratman (Universitas Tadulako, 2021)
This study aimed to determine the effect of the inquiry learning model on the learning outcomes of student SMAN 1 Banawa Tengah on buffer solution material. This type of research was a quasi-experimental, with a nonequivalent control group design. The sample used in this study was students of class XI IPA 1 as an experimental class with 34 students and class XI IPA 2 as a control class with 34 students. Testing of the research data used 2-party t-test with prerequisite tests, normality and homogeneity tests. The results of data analysis obtained, the average value of the experimental class was 75.5 and the control class was 66.97. The results of hypothesis testing with independent sample t test obtained that sig value (p) = 0.010 with the test criteria α = 5% (0.05), then H0 was rejected and H1 was accepted, so it can be concluded that the inquiry learning model influences students’ learning outcomes.